(untitled) (Research, Society and Development, 2021)
Objective: To analyze the impact of the pandemic on the mental health of pregnant and postpartum women, listing the main predictors ofworsening maternal psychiatric clinic. Methods: Integrative Literature Review, which articles were searched in the Scientific Electronic Library Online (SciELO), PUBMED and Latin American and Caribbean Literature (LILACS) databases. Twenty-nine published articles between 2019 and 2021 were included in this study. Results: Due to the advent of the covid-19 pandemic, studies show that pregnant women are experiencing high levels of anxiety and depressive symptoms, diverging from pre-covid period in which such psychiatric disorders had a lower incidence of reported cases. Furthermore, longer periods of quarantine are related to more severe psychological distress. Also, it was possible to observe in the literature that women who already had compromised mental health from the beginning of pregnancy are at increased risk of developing postpartum depression, in which cases breastfeeding until the 3rd month of the puerperium is a protective factor. Final Considerations: Added to all the changes and adaptations already expected in pregnancy, pregnant women deal with the side effects of covid-19. Thus, there is a direct relationship between the SARS-CoV-2 pandemic and the serious psychological challenges, which generate a potential increase in the incidence of anxiety, depression among pregnant women, as well as postpartum depression in postpartum women.